Factorise completely ( x − 4x^3)

(x-4x3) = x(1-4x2)  Just taking a factor of x out of both terms Within the inner bracket we have a difference of two squares. 12=1 and (2x)2=4x2 therefore we can write x(1-4x2) = x(1-2x)(1+2x) 

Answered by Edward C. Maths tutor

19539 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

If n is an integer prove (n+3)^(2)-n^(2) is never even.


Find the equation of the normal to the curve x^3 + 2(x^2)y = y^3 + 15 at the point (2, 1)


Using the product rule, differentiate: y = (x^2 - 1)(x^3 + 3).


Solve the simultaneous equations: y - 3x + 2 = 0 y^2 - x - 6x^2 = 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences